Individual differences monitoring dosage reactions - Paužaitė, S. (Psichologija, 1965)
One of the major problems of engineering psychology is dosage reactions. The purpose of the article is to find out what the individual differences in dosage reactions are. The influence of individuals’ motion transmission increase and compliance or non-compliance of the structure of the governing body and the indicator scale were experimentally examined. Individual psychological differences become apparent at different latent periods, show different dosage response time, relationships between the latent period the length, reaction times, and rates of organ movement. Based on experimental data we can conclude that the duration of the action, it appears, is associated with nervous processes motility. For subjects with a short latency period dosage reactions are also significantly shorter. This demonstrates the great nervous process motility of the research subjects. The latent period duration also shows speed the emergence of neural processes, while organ speed and motion termination describes differential attenuation. The operators of individual psychological differences should be taken into account, not merely teaching and training them, but also selecting them.